Opening a M. Sc. in Electrical Engineering for non-traditional Students - Müller, Anja Lina; Schwarzbacher, Andreas; Hoppe, Bernhard (International Journal of Advanced Corporate Learning (iJAC), 2012)
This paper will discuss why and how the University of Applied Sciences, Darmstadt/Germany will identify core competences of bachelorâ??s degrees in Electronic Engineering and develop specially tailored life-long learning programmes for non-traditional students. These programmes will enable highly qualified master craftsmen, solely educated to the level of master craftsmen, to successfully participate in the existing Master of Science in Electronic Engineering programme. Furthermore, this paper will present the initial results obtained from a pilot project group.